TeleMed II single board computer implementation of a Linux-based telemedical system - Daguimol, Brent Josef H.
Telemedicine is the use of communications technology in delivering healthcare services. It is producing great impact on patient monitoring in remote and non-clinical locations. Rural areas in the Philippines have little or no access to quality healthcare. The implementation of a telemedical system will greatly benefit these communities. Telemed II is the next phase in the development of The National Telehealth Service Program. The first phase was TeleMed: A Linux-based Telemedical System. The previous project was able to design a telemedical system consisting of commercially available biomedical devices connected to a remote workstation, called the RxBox, via serial port The existing RxBox communicates with the doctor's workstation via ethernet Local Area Network (LAN). Software applications that allow video conferencing and instant messaging between the RxBox and the doctor's workstation were also developed in the said project. The main objective of TeleMed II is to implement the RxBox, in a single board computer instead of a standard personal computer. This is to make the unit portable. The biomedical modules will now be connected to the RxBox through Universal Serial Bus (USB) ports to allow expandability, since computers generally have more USB ports than serial ports. Also, the project aims to improve on the existing software developed from the previous project and implement it on the new RxBox. Finally, a set of PSoC-based biomedical devices which are vital for continuously monitoring the patients' conditions were developed. The vital health parameters to be monitored include the ECG, pulse rate, percent oxygenation of blood, and blood pressure. The project involves digitizing the acquired analog signals taken from three biomedical instruments, an electrocardiogram (ECG) device, a blood pressure module, and a pulse oximeter. The project utilizes a previously developed ECG module from the Instrumentation, Robotics, and Control (IRC) Laboratory. Blood pressure measurements and pulse oximetry will be done using a pressure sensor and a finger sensor, respectively. The CY8C24792-24LFXI Programmable System-on-chip (PSoC) will be used to perform the analog-to-digital signal conversion for the ECG and to transfer data from the modules to the RxBox via USB port. Each module will be equipped with an LCD user interface that will locally display outputs. The RxBox runs on a Linux operating system. A Graphical User Interface (GUI) program installed in the RxBox displays the received data and sends it to the doctor's workstation. The project also provides methods for the end-users to interact with each other. Both the RxBox and the doctor's workstation have Instant Messaging (IM) and video conferencing features that were implemented using existing open-source applications.